Green pills: making corporate climate commitments credible - Armour, J; Enriques, L; Wetzer, T (University of Arizona, 2023)
Many of the world’s largest firms are now announcing plans to reduce their carbon emissions over the coming decades. Against the backdrop of lackadaisical climate policy, this development is widely held out as positive. But ubiquitous allegations of corporate and investor greenwashing raise the question of just how credible these announcements really are. After all, even when firms propose rigorous emission reduction targets, the shifting sands of investor preferences raise the risk that companies eventually renege. Given the rising proportion of investors with climate-conscious preferences, this leaves money on the table: firms engaging in a genuine transition away from high-emission activity should benefit from higher valuations, creating a business case to commit credibly. Conventional mechanisms to generate such credible climate commitments––climate disclosures, corporate governance reforms, or changes to the corporate purpose––are inadequate to achieve that goal. Instead, we propose a suite of contractual mechanisms, which we term “green pills,” to make climate commitments credible by endogenizing incentives to meet climate targets. We argue that their adoption does not contravene directors’ fiduciary duties and requires no change to corporate law. Green pills thus help firms and their investors undertake credible climate commitments and show other stakeholders how serious they really are about their contribution to tackling climate change.